Supervised curricular internship and training of the nurse: developed activities - Tierle Kosloski Ramos; Elisabeta Albertina Nietsche; Silvana Bastos Cogo; Liege Gonçalves Cassenote; Andressa Böck; Fernanda Soares Martins (Universidade Federal de Santa Maria, 2018)
Aim: to analyze the activities developed during the Curricular Supervised Internship by nursing students and residents of a multiprofessional program and its influences on training. Method: this is a field research with a descriptive and exploratory qualitative approach. For the data collection, the semi-structured interview technique was used. The process of data analysis, together with the discussion and interpretation are based on the Bardin Content Analysis technique. Results: from the participants' contribution, three categories were identified: welfare activities, management activities and educational activities. Final considerations: the curricular supervised internship presents itself as an activity in which it is possible to develop and enhance the skills and competences required in the profile of the professional nursing egress. It was possible to identify the presence of assistance, management and educational activities in accordance with what is recommended by the National Curricular Guidelines. It was also identified that there is a need for greater emphasis still on the graduation of nurses' private activities.